Rancangan gelang pintar untuk siswa tunarungu menggunakan metode Quality Function Deployment - Tumewu, Tryadi Wilhelmus; Singgeta, Ryan Laksmana; Rachmadi, Ronald Albert; Raton, Yulius Christian; Rottie, Ronaldo Ignasius Ferdy (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Improving the quality of life for deaf students with special needs, the development of assistive technology is crucial to aid in the classroom learning process. This research aims to design an assistive technology in the form of a Smartband that is beneficial for helping deaf students to interact, understand instructions, and engage in social interactions. The design of this smartband employs the Quality Function Deployment method to ensure that the needs and desires of deaf students are met in the designed device. Based on the analysis of questionnaires from 43 deaf students, eight Customer Requirements were identified. The top priorities for development were voice call detection (14.2%), surrounding hazard alerts (13.99%), and notification capabilities (13.49%). By utilizing the Relationship Matrix in the House of Quality, the Technical Priorities to be developed were determined, namely a voice recognition sensor (19% with a technical importance score of 135), followed by ESP32 and Vibration Motor (16% with a technical importance score of 117). The designed smart bracelet functions well but requires further evaluation, especially in terms of aesthetics, as the current respondents were limited and did not differentiate based on age, which is known to have varying preferences.